Efektivitas Komunikasi dalam Penyuluhan Sistem Tanam Jajar Legowo pada GAPOKTAN Sumber Mulyo di Desa Kediren, Kecamatan Kalitengah, Kabupaten Lamongan, Jawa Timur - VIVI ANITA ACHMAD; I DEWA PUTU OKA SUARDI; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Effectiveness of Communication in Counseling Jajar Legowo Planting System onGAPOKTAN Sumber Mulyo in the Village Kediren, Sub-district Kalitengah Lamongan Regency, East Java. Increased productivity of rice farming is needed in order of the community. Theinnovation of the Jajar Legowo planting system is expected to bring about an increase inthe results of farming. One of the Gapoktan implementing Jajar Legowo plantingsystem is GAPOKTAN Sumber Mulyo. Facts on the field show that rice yields usingthe Jajar Legowo planting system did not increase compared to using a tile system. Thiswas allegedly due to communication carried out by extension agents to farmers.Farmers do not understand the explanation given by extension workers. Therefore, it isnecessary to conduct research on communications conducted by extensionagents.Communication can be effective if there is understanding, pleasure, attitude,good relationship, and action. The research location is located in Kediren Village,Kalitengah District, Lamongan Regency. The purpose of this study was to determine theeffectiveness of communication in the extension of the Jajar Legowo planting system onGAPOKTAN Sumber Mulyo. The analytical method used is qualitative descriptiveanalysis.Based on the results of the study it can be concluded the extension of the JajarLegowo planting system is effective. The effectiveness of the communication is shownby: (1) farmers understand the Jajar Legowo planting system; (2) farmers enjoy the Jajar Legowo planting system; (3) farmers sympathize with the Jajar Legowo plantingsystem; (4) the relationship between farmers and extension workers is very good; and(5) the application of Jajar Legowo planting system in accordance with therecommendations of the instructor. Based on the results of the study, discussion, andconclusions, it can be suggested: (1) the need for counseling to members ofGAPOKTAN Sumber Mulyo to use organic fertilizer in farming so that agriculturalland remains fertile and can be used for mina rice; (2) farmers can revive a culture ofmutual cooperation in planting so that it does not require large costs; (3) extensionagents can conduct counseling using cyber extention methods is farmers can learn thematerial neeses through the internet.